Childhood Adversity and Energy Poverty - Zhiming Cheng; Liwen Guo; Russell Smyth; Massimiliano Tani (Institute of Labor Economics (IZA), 2021)
We use data from China Family Panel Studies to examine the effects of being a child or adolescent in China's Great Famine on the likelihood of being in energy poverty in adulthood. We find that a one unit increase in the intensity of the Famine, measured by the number of excess deaths per 100 people, is associated with a 1.8-3.5 percentage points decline in the probability of being in energy poverty in adulthood, depending on the exact specification and measure of energy poverty. We find that personal income is a channel through which being a child or adolescent during the Great Famine affects the proclivity to be in energy poverty later in life. These findings are robust to alternative ways of measuring childhood adversity and energy poverty.
Keywords: J13; I32; Q41; 330; childhood adversity; energy poverty; China; the Chinese Great Famine